Silicon based photodetector with Ru(II) complexes organic interlayer - Karabulut, Abdulkerim; Dere, A.; Dayan, Osman; Al-Sehemi, Abdullah G.; Serbetci, Z.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2019)
In present work, the electrical properties and illumination effects were investigated for the silicon based photodetector with organic Ru(II) complexes interfacial layer. The current-voltage (I-V) and capacitance/conductance-voltage (C/G-V) measurements were analyzed to determine electrical and photoelectrical properties under dark and different solar light intensity conditions. The reverse bias current values under light conditions were higher than dark conditions, and this situation demonstrates that the fabricated device displays a photo conducting behavior. Besides, some crucial electrical parameters such as series resistance, barrier height and ideality factor values of prepared device were calculated by using current-voltage measurements. The ideality factor and barrier height values of fabricated device were calculated as 9.42 and 0.59 for dark condition. Besides to these experiments, transient photocurrent and photo-capacitance/conductance were also investigated under different light conditions. It was determined from transient measurements that the fabricated device has a high sensitivity to light. The photoresponse of the diode was determined to be around 4479 +/- 1.9 under 100 mW/cm(2 )illumination. The examined C/G-V characteristics of the fabricated device strongly depend on voltage and frequency. The analyzed results suggest that the fabricated Al/Ru(II) complexes/p-Si/Al device can be used in rapidly developing optoelectronic applications, especially for the organic materials-based photodetector technology.
Keywords: Morphological analyses; Electrical properties; Ru(II) complexes; Photodetector; Illumination effect